Increase of efficiency of the automated systems of powder firefighting by the use of vibro-vortical technologies - Potekha, Алексей Валентинович (Chrezvychaynye situatsii: obrazovanie i nauka, 2007)
It is shown that the use of vortical and vibrating technologies allows by the method of stable maintenance of fluid state of fire extinguishing powder to increase the efficiency of systems of powder firefighting.